Frontispiece: HSO2+ Formation from Ion‐Molecule Reactions of SO2⋅+ with Water and Methane: Two Fast Reactions with Reverse Temperature‐Dependent Kinetic Trend. Issue 28 (17th May 2017) - Cartoni, Antonella; Catone, Daniele; Bolognesi, Paola; Satta, Mauro; Markus, Pal; Avaldi, Lorenzo
Abstract : Dynamics in Hydrogen‐Atom‐Transfer (HAT) reactions . The HAT reactions of SO2 .+ with H2 O and CH4 lead to the formation of the HSO2 + with different trend by increasing the internal energy of SO2 .+ : the yield of the product decreases in the case of H2 O, whereas it firstly decreases and then increases in the reaction with CH4 . DFT and Variational‐Transition‐State‐Theory calculations reproduce both pathways unraveling the peculiar nature of their different reaction efficiency. For more details see the Full Paper by A. Cartoni, M. Satta et al. onpage 6772 ff.